Minat Siswa Terhadap Ekstrakurikuler Tari Di SMP Negeri 34 Padang - Dike Septia Dolly; Susmiarti Susmiarti (SENDRATASIK UNP, 2020)
This research aims to determine and describe students' interest in dance extracurricular activity at SMP Negeri 34 Padang. This type of research was a qualitative study with using descriptive method. The instrument in this study was the researcher. The additional instrument used the questionnaire. Techniques of Data collection were carried out by taking observation, questionnaires, documentation and practicing motion. The types of data in this study were primary and secondary data. Data were analyzed by using the percentage formula. The results show that students' interest in dance extracurricular activity at SMP Negeri 34 Padang is relatively good. The percentage of the students feeling happy in dance extracurricular is 52.78% that is classified as moderate, students' interest in dance extracurricular is 48.33% that is moderate, the student’s attention on dance extracurricular is 45.56% that is classified as moderate and the student's interest towards dance extracurricular is 47, 78% that is classified as moderate. It can be concluded that the students' interest in dance extracurricular activity in SMP Negeri 34 Padang is good with an average value is 64.81%. There are several things that need to be organized in this dance extracurricular activity so that students' interest in this activity will increase even more in terms of material and method.